Design of a compact and miniature band-pass filter for global positioning system applications - Amal Kadiri; Abdelali Tajmouati; Jamal Zbitou; Issam Zahraoui; Mohamed Latrach (Institute of Advanced Engineering and Science, 2022)
In this paper, a novel compact band pass filter (BPF) is proposed for global positioning system (GPS) applications. The proposed filter which is based on a microstrip resonator is mounted on a low cost RO4000 substrate with a dielectric constant εr=3.5, a thickness h=1.542 mm, a loss tangent tan (δ)=0.0027. It has a bandwidth from 1.55 GHz to 1.72 GHz. This filter is optimized and validated by using two electromagnetic solvers. The area occupied by this BPF is 33.6×41.24 mm2. The final circuit is a low cost BPF and can be associated with passive and active circuits due to the miniature dimensions.